Discourses on Professional Learning
XIV, 395 p. 38 illus., 16 illus. in color.
Keywords: This book analyses and elaborates on learning processes within work environments and explores professional learning. It presents research indicating general characteristics of the work environment that support learning, as well as barriers to workplace learning. Themes of professional development, lifelong learning and business organisation emerge through the chapters, and contributions explore theoretical and empirical analyses on the boundary between working and learning in various contexts and with various methodological approaches. Readers will discover how current workplace learning approaches can emphasise the learning potential of the work environment and how workplaces can combine the application of competence, that is working, with its acquisition or learning. Through these chapters, we learn about the educational challenge to design workplaces as environments of rich learning potential without neglecting business demands. Expert authors explore how learning and working are both to be considered as two common aspects of an individual’s activity. Complexity, significance, integrity, and variety of assigned work tasks as well as scope of action, interaction, and feedback within its processing, turn out to be crucial work characteristics, amongst others revealed in these chapters. Part of the Professional and Practice-based Learning series, this book will appeal to anyone with an interest in workplaces as learning environments: those within government, community or business agencies and within the research communities in education, psychology, sociology, and business management will find it of great interest.